Dichotomous Perception of Animal Categories in Infancy - White, Hannah (Vis cogn, 2018)
Although there is a wealth of knowledge on categorization early in life, there are still many unanswered questions about the nature of category representation in infancy. For example, it is unclear whether infants are sensitive to boundaries between complex categories, such as types of animals, or whether young infants exhibit such sensitivity without explicit experience in the lab. Using a morphing technique, we linearly altered the category composition of images and measured 6.5-month-olds’ attention to pairs of animal faces that either did or did not cross the categorical boundary, with the stimuli in each pair being equally dissimilar from one another across the two types of image pairs. Results indicated that infants dichotomize the continua between cats and dogs and between cows and otters, but only when the images are presented in their canonical, upright orientations. These findings demonstrate a propensity to dichotomize early in life that could have implications for social categorizations, such as race and gender.